2006
DOI: 10.1042/bj20060696
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of GLUT4 gene expression by SREBP-1c in adipocytes

Abstract: Expression of the GLUT4 (glucose transporter type 4 isoform) gene in adipocytes is subject to hormonal or metabolic control. In the present study, we have characterized an adipose tissue transcription factor that is influenced by fasting/refeeding regimens and insulin. Northern blotting showed that refeeding increased GLUT4 mRNA levels for 24 h in adipose tissue. Consistent with an increased GLUT4 gene expression, the mRNA levels of SREBP (sterol-regulatory-element-binding protein)-1c in adipose tissue were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 61 publications
3
33
0
4
Order By: Relevance
“…Recently, we showed a direct relationship between SREBP1c and GLUT4 gene expression. We identified the SREBP responsive element (SRE) in the bases 7109 and 7100 bp region of the human GLUT4 promoter (43). We also confirmed the Sp1 binding site on the human GLUT4 promoter.…”
Section: Sterol Response Element Binding Protein-1c (Srebp-1c) and Sp1supporting
confidence: 60%
See 1 more Smart Citation
“…Recently, we showed a direct relationship between SREBP1c and GLUT4 gene expression. We identified the SREBP responsive element (SRE) in the bases 7109 and 7100 bp region of the human GLUT4 promoter (43). We also confirmed the Sp1 binding site on the human GLUT4 promoter.…”
Section: Sterol Response Element Binding Protein-1c (Srebp-1c) and Sp1supporting
confidence: 60%
“…Muscle GLUT4 enhancer factor (mGEF) and myocyte enhancer factor 2 (MEF2), which are regulated by AMP-activated protein kinase (AMPK), also synergistically control GLUT4 gene expression (41). MyoD (42), nuclear factor I (NF-1) family (37), C/EBP-a (29), SREBP-1c (43), and O/E-1 factor (39) are known to be responsible for insulin-mediated GLUT4 gene expression. Those factors, which are responsible for the organization of the tissue specificity of GLUT4 gene, will be described in this section (Figs 2 and 3).…”
Section: Transcriptional Activators Of Glut4 Genementioning
confidence: 99%
“…From another standpoint, it was found that 24 h blockade of the CB1 receptor increases the binding activity of SREBP-1, a positive regulator of Slc2a4 gene expression (Im et al 2006), to the Slc2a4 promoter; thus, this finding contributes to the increased Slc2a4 mRNA expression observed in this condition.…”
Section: Discussionmentioning
confidence: 91%
“…To address the hypothesis that SREBP-1 may be involved in Slc2a4 upregulation by CB1 receptor, the described SRE site of Slc2a4 promoter was utilized in EMSA experiments (Im et al 2006). To examine the specificity of the nuclear protein binding into the labeled oligonucleotide containing the SRE binding site, a competition with unlabeled SRE oligonucleotide was performed (Fig.…”
Section: Chronic But Not Acute Cb1 Antagonism Increases Srebf1 Type Amentioning
confidence: 99%
“…In this case, SREBP inhibits caveolin gene transcription in contrast to its stimulating effect on other gene promoters [27,28] . Caveolin-1, a type of free cholesterolbinding protein, is another significant protein involved in cholesterol homeostasis [29] .…”
Section: Discussionmentioning
confidence: 99%